Experimental Analysis on Titanium Grade-V Sheet Using Laser Beam Machining Process - Rakesh Kumar, Satish Namdev, Anand Pandey, Arun Kr. Pandey (International Journal of Advanced Science and Technology, 2019)
Orthopaedical implantation is a challenging task because human made body parts must be biocompatible and their working should be same as natural body parts. Medical implants are mainly fabricated by titanium grade V because of its biocompatibility and strength. Body part implantation improve work efficiency of physically disabled person. So, it is necessary that body part must work or movement as natural body part. Small size holes are provided to join bio compatible with natural body part. Precise micro size hole fabrication is very difficult task on titanium alloys. In present work, 1mm and 2mm diameters hole have been fabricated on biocompatible material (Ti-6AL-4V) through laser drilling process within range of selected parameters. Hole geometrical features have been compared on the basis effect of input parameters for two different hole diameters. CCRD has been used to prepare design of experiments. ANOVA technique also used for model validation for responses hole circularity, hole taper, heat affected zone and decided significant parameters for different size of hole.